An anthropological introduction to YouTube - Wesch, Michael (My University, 2010)
Recording of a lecture titled "The Anthropology of YouTube,” given by Michael Wesch on June 23, 2008 at the Library of Congress, Washington, D.C.
Keywords: YouTube; Video; New media; Communication; Human interaction